Longitudinal wastewater-based surveillance of SARS-CoV-2 during 2023 in Ethiopia - Abera Dinssa, Daniel; Gebremicael, Gebremedhin; Mengistu, Yohannes; Hull, Noah C.; Chalchisa, Dinknesh; Berhanu, Girma; Gebreegziabxier, Atsbeha; Norberg, Ashley; Snyder, Sarah; Wright, Sarah; Gobena, Waktole; Abera, Adugna; et al. (Frontiers in Public Health, 2024)
Introduction: Although wastewater-based epidemiology successfully functioned as a tool for monitoring the COVID-19 pandemic globally, relatively little is known about its utility in low-income countries. The aims of this study were to quantify SARS-CoV-2 RNA in wastewater, estimate the number of infected individuals in the catchment areas, and correlate the results with the clinically reported COVID-19 cases in Addis Ababa, Ethiopia. Methods: A total of 323 influent and 33 effluent wastewater samples were collected from three Wastewater Treatment Plants (WWTPs) using a 24-hour composite Moore swab sampling method during February to October 2023. The virus was captured using Ceres Nanotrap® Enhancement Reagent 2 and Nanotrap® Microbiome A Particles, and then nucleic acids were extracted using the Qiagen QIAamp Viral RNA Mini Kit. The ThermoFisher TaqPath™ COVID-19 kit was applied to perform real time reverse transcriptase polymerase chain reaction (qRT-PCR) to quantify the SARS-CoV-2 RNA. Wastewater viral concentrations were normalized using flow rate and number of people served. Spearman correlation was used to compare the SARS-CoV-2 target gene concentration to the reported COVID-19 cases, in the sampling period. The numbers of infected individuals under each treatment plant were calculated taking in to account the concentration of the target genes, the flow rate of treatment plants, gram of feces per person-day and RNA copies per gram of feces. Result: SARS-CoV-2 was detected in 94% of untreated wastewater samples. All effluent wastewater samples (n=22) from Upflow Anaerobic Sludge Blanket reactor and Membrane Bio-reactor technology were SARS-COV-2 RNA negative, whereas two out of eleven effluents from Waste Stabilization Pond were found positive. Positive correlations were observed between the weekly average SARS-CoV-2 concentration and the cumulative weekly reported COVID-19 cases in Addis Ababa. The estimated number of infected people in Kality Treatment catchment area was 330 times the number of COVID-19 cases reported during the study period in Addis Ababa. Discussion: This study revealed that SARS-CoV-2 was circulating in the community and confirms previous reports of more asymptomatic COVID-19 cases in Ethiopia. Additionally, this study provides further evidence on the importance of wastewater based surveillance in general to monitor infectious diseases in low-income settings.